Health workers and vaccination coverage in developing countries: an econometric analysis - Anand, Sudhir; Bärnighausen, Till (The lancet, 2007)
Background: Vaccine-preventable diseases cause more than 1 million deaths among children in developing countries every year. Although health workers are needed to do vaccinations, the role of human resources for health as a determinant of vaccination coverage at the population level has not been investigated. Our aim was to test whether health worker density was positively associated with childhood vaccination coverage in developing countries. Methods: We did cross-country multiple regression analyses with coverage of three vaccinations-measles-containing vaccine (MCV); diphtheria, tetanus, and pertussis (DTP3); and poliomyelitis (polio3)-as dependent variables. Aggregate health worker density was an independent variable in one set of regressions; doctor and nurse densities were used separately in another set. We controlled for national income per person, female adult literacy, and land area. Findings: Health worker density was significantly associated with coverage of all three vaccinations (MCV p=0·0024; DTP3 p=0·0004; polio3 p=0·0008). However, when the effects of doctors and nurses were assessed separately, we found that nurse density was significantly associated with coverage of all three vaccinations (MCV p=0·0097; DTP3 p=0·0083; polio3 p=0·0089), but doctor density was not (MCV p=0·7953; DTP3 p=0·7971; polio3 p=0·7885). Female adult literacy was positively associated, and land area negatively associated, with vaccination coverage. National income per person had no effect on coverage. Interpretation: A higher density of health workers (nurses) increases the availability of vaccination services over time and space, making it more likely that children will be vaccinated. After controlling for other determinants, the level of income does not contribute to improved immunisation coverage. Health workers can be a major constraining factor on vaccination coverage in developing countries.